2023
DOI: 10.1039/d2ob02332f
|View full text |Cite
|
Sign up to set email alerts
|

Resorculins: hybrid polyketide macrolides from Streptomyces sp. MST-91080

Abstract: Fourteen-membered macrolides are a class of compounds with significant clinical value as antibacterial agents. As part of our ongoing investigation into the metabolites of Streptomyces sp. MST-91080, we report the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Next, we wanted to demonstrate the flexibility of getphylo to analyse other genetic elements. To demonstrate this, we reconstituted the evolutionary history of the resorculin BGC 15 (Case Study 2). getphylo successfully identified the conserved genes for 3,5-dihydroxybenzoic acid biosynthesis, in line with recently published results 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we wanted to demonstrate the flexibility of getphylo to analyse other genetic elements. To demonstrate this, we reconstituted the evolutionary history of the resorculin BGC 15 (Case Study 2). getphylo successfully identified the conserved genes for 3,5-dihydroxybenzoic acid biosynthesis, in line with recently published results 15 .…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate this, we reconstituted the evolutionary history of the resorculin BGC 15 (Case Study 2). getphylo successfully identified the conserved genes for 3,5-dihydroxybenzoic acid biosynthesis, in line with recently published results 15 . This demonstrates getphylo's ability to build phylogeny for non-genome scale genetic elements, a function that will aid in the research of plasmids, phages and other gene clusters.…”
Section: Resultsmentioning
confidence: 99%
“…MST-91080, is a 3,5-dihydroxybenzoic acid-derived macrolide. 16 Analysis of the resorculin biosynthetic gene cluster has revealed that it is a hybrid of type I and type II polyketide synthases (PKSs).…”
mentioning
confidence: 99%
“…New 14-membered macrolides derived from 3,5-dihydroxybenzoic acid, such as resorculin A 20 , have been discovered from Streptomyces species MST-91080. 18 Genome sequencing revealed that the resorculin biosynthetic gene cluster is a hybrid of type I and type III polyketide synthases (PKSs). Genome mining of Streptomyces cinnamoneus ATCC 21532 has identified a type I/type III PKS hybrid that generates macrolides, including cinnamomycin A 21 , from 3,5-dihydroxybenzoic acid.…”
mentioning
confidence: 99%
“…membered macrolides derived from 3,5-dihydroxybenzoic acid, such as resorculin A 20, have been discovered from Streptomyces species MST-91080 18. Genome sequencing revealed that the resorculin biosynthetic gene cluster is a hybrid of type I and type III polyketide synthases (PKSs).…”
mentioning
confidence: 99%